Impact assessment of a co‐optimized dynamic line rating and transmission switching topology on network expansion planning. (3rd June 2020) - Numan, Muhammad; Feng, Donghan; Abbas, Farukh; Rahman, Usama; Wattoo, Waqas Ahmad
Summary: Power system planning needs regular investment in transmission area to cope with the increasing load, network congestion, and large‐scale integration of renewable generation. With the growth of renewable energy resources integration, electric utilities are faced with an increasingly complex operating environment. Utilities are in need of a series of cost‐effective technologies which allow them to operate power systems more economically and reliably. Optimal transmission switching (OTS) and dynamic line rating (DLR) are such cost‐effective technologies which offer potential solution to improve power system operation and reliability. This article develops a co‐optimized network expansion planning (CONEP) model to devise an optimal investment plan for building new transmission lines and generating units while simultaneously incorporating OTS and DLR topologies. The optimization problem using CONEP is modeled as a mixed‐integer linear programming problem. The objective of the optimal investment plan is to minimize the total investment cost while satisfying the planning and operational constraints. The model identifies the location, time, and number of the candidate lines/units to be invested in the planning horizon. In addition, the investment plan determines when and which line should be switched off from the network and which line should be upgraded to adopt DLR values. Installing the optimal set of candidate lines and units will not only fulfill the anticipated future demand but will also improve power system reliability. Utilizing the modified IEEE 24‐bus system, sensitivity analyses are performed to characterize the impact of the load growth, discount rate, number of lines adopting DLR, and number of line switching actions on the expansion planning. Numerical results establish that the enforcement of DLR and the practice of OTS are complementary in the expansion model and can improve cost of the investment on the IEEE 118‐bus system up to 20.78%.